Characterization of Plasmodium falciparum ATP-dependent DNA helicase RuvB3. (December 2016) - Limudomporn, Paviga; Moonsom, Saengduen; Leartsakulpanich, Ubolsree; Suntornthiticharoen, Pattra; Petmitr, Songsak; Weinfeld, Michael; Chavalitshewinkoon-Petmitr, Porntip
Abstract Background Malaria is one of the most serious and widespread parasitic diseases affecting humans. Because of the spread of resistance in both parasites and the mosquito vectors to anti-malarial drugs and insecticides, controlling the spread of malaria is becoming difficult. Thus, identifying new drug targets is urgently needed. Helicases play key roles in a wide range of cellular activities involving DNA and RNA transactions, making them attractive anti-malarial drug targets. Methods ATP-dependent DNA helicase gene (PfRuvB3 ) ofPlasmodium falciparum strain K1, a chloroquine and pyrimethamine-resistant strain, was inserted into pQE-TriSystem His-Strep 2 vector, heterologously expressed and affinity purified. Identity of recombinant PfRuvB3 was confirmed by western blotting coupled with tandem mass spectrometry. Helicase and ATPase activities were characterized as well as co-factors required for optimal function. Results Recombinant PfRuvB3 has molecular size of 59 kDa, showing both DNA helicase and ATPase activities. Its helicase activity is dependent on divalent cations (Cu2+, Mg2+, Ni+2 or Zn+2 ) and ATP or dATP but is inhibited by high NaCl concentration (>100 mM). PfPuvB3 is unable to act on blunt-ended duplex DNA, but manifests ATPase activity in the presence of either single- or double-stranded DNA. PfRuvB3.is inhibited by doxorubicin, daunorubicin and netropsin, known DNA helicase inhibitors. Conclusions Purified recombinant PfRuvB3 contains both DNA helicase and ATPase activities. Differences in properties of RuvB between the malaria parasite obtained from the study and human host provide an avenue leading to the development of novel drugs targeting specifically the malaria form of RuvB family of DNA helicases.